2021
DOI: 10.3389/fgene.2021.598575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Circular RNA of Chicken Growth Hormone Receptor Gene on Cell Proliferation

Abstract: Animal growth and development are regulated by neural and endocrine growth axes, in which cell proliferation plays key roles. Recently, many research showed that circular RNAs were involved in hepatocyte and myoblast proliferation. Previously, we identified a circular RNA derived from the chicken GHR gene, named circGHR. However, the function of circGHR is unclear. The objective of this study was to investigate circGHR expression pattern and its roles in cell proliferation. Results indicated that circGHR was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Circ-GHR is reduced in the leg and pectoral muscles steadily from E13 to 7 w. It is positively correlated with GHR, and overexpressing Circ-GHR will promote myoblast proliferation. It is hypothesized that Circ-GHR may promote myoblast proliferation by regulating the expression of GHR mRNA and GH binding protein ( GHBP ), but it has been demonstrated to have no significant effect in DF-1 cell lines, so the definitive mechanism needs to be further explored [ 108 ].…”
Section: Circrna Modulates Skeletal Muscle In Domestic Chickensmentioning
confidence: 99%
“…Circ-GHR is reduced in the leg and pectoral muscles steadily from E13 to 7 w. It is positively correlated with GHR, and overexpressing Circ-GHR will promote myoblast proliferation. It is hypothesized that Circ-GHR may promote myoblast proliferation by regulating the expression of GHR mRNA and GH binding protein ( GHBP ), but it has been demonstrated to have no significant effect in DF-1 cell lines, so the definitive mechanism needs to be further explored [ 108 ].…”
Section: Circrna Modulates Skeletal Muscle In Domestic Chickensmentioning
confidence: 99%
“…The pre-RNA of the GHR gene can be back spliced to form a circular transcript (circGHR) in human, mouse and chicken [ 16 ]. We previously performed high-throughput RNA sequencing of chicken liver and muscle, finding that chicken circGHR could promote the proliferation of primary myoblasts [ 22 ]. In addition, we found that mouse circGHR was formed by backward splicing of exons 2 and 8 of the GHR gene.…”
Section: Introductionmentioning
confidence: 99%
“…3), indicating that GC proliferation could be induced. A review of the literature revealed that chicken circGHR positively regulates hepatocyte and myoblast proliferation (Xu et al 2021), and by binding to miR-204, circFNDC3AL increases the expression of BCL9 and encourages the growth and differentiation of SMSCS in chickens (Wei et al 2021). Moreover, circRNAs in follicular GCs are widely distributed at various developmental stages (Shen et al 2019).…”
mentioning
confidence: 99%